2008
DOI: 10.4161/chan.2.3.6188
|View full text |Cite
|
Sign up to set email alerts
|

Role of the fourth membrane domain of the NR2B subunit in the assembly of the NMDA receptor

Abstract: N-methyl-D-aspartate (NMDA) receptors play crucial roles in excitatory synaptic transmission as well as in excitotoxicity. A growing body of evidence suggests that the regulation of both subunit composition and the number of NMDA receptors reaching the surface membrane are tightly regulated. Recently, we have shown that the third membrane domains (M3) of both NR1 and NR2B subunits contain endoplasmic reticulum (ER) retention signals that prevent the unassembled subunits from leaving the ER. Furthermore, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…However, a later study proposed that the HLFY motif is not necessary for the formation of the surface functional NMDAR, as it can be replaced by alanines if the C-terminus is absent (Yang et al, 2007 ). Similarly, the deletion of the GluN2B C-terminus including the HLFY motif did not affect the formation of functional receptors when two pieces of the GluN2B subunit, GluN2B truncated before M4 domain and GluN2B M4 domain, were co-expressed together with the GluN1 subunit (Horak et al, 2008a ). Together, these data indicate that the HLFY motif may provide a structural role to ensure the proper orientation of the membrane domains and/or the C-termini in the ER processing of the GluN1/GluN2 receptors.…”
Section: Processing Of Nmdars In the Ermentioning
confidence: 99%
“…However, a later study proposed that the HLFY motif is not necessary for the formation of the surface functional NMDAR, as it can be replaced by alanines if the C-terminus is absent (Yang et al, 2007 ). Similarly, the deletion of the GluN2B C-terminus including the HLFY motif did not affect the formation of functional receptors when two pieces of the GluN2B subunit, GluN2B truncated before M4 domain and GluN2B M4 domain, were co-expressed together with the GluN1 subunit (Horak et al, 2008a ). Together, these data indicate that the HLFY motif may provide a structural role to ensure the proper orientation of the membrane domains and/or the C-termini in the ER processing of the GluN1/GluN2 receptors.…”
Section: Processing Of Nmdars In the Ermentioning
confidence: 99%
“…Previous studies identified other regions in GluN subunits besides LBDs, including ATD (Qiu et al, 2009), M3 domains (Horak et al, 2008), and CTDs (Standley et al, 2000; Scott et al, 2001; Xia et al, 2001; Horak and Wenthold, 2009), containing ER retention and export signals. Therefore, we anticipate that future studies will investigate at what level other ER retention and export signals contribute to regulating the surface expression of the GluN1/GluN2 receptors with mutated LBDs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HLFY motif on the end of TM4 in the GluN2B subunit, which is not present in GluN1 subunits, was found to likely be involved in the export of NMDARs (Hawkins et al, 2004). Replacing each of these key residues with alanine, or truncating the GluN2B before the TM4 domain was found to disturb the surface trafficking of functional receptors (Yang et al, 2007;Horak et al, 2008a). It is believed that this motif may play a role as a conformational signal, ensuring proper orientation of the receptor domains.…”
Section: Cellular Events Involved In the Forward Trafficking And Memb...mentioning
confidence: 99%
“…The key amino acids Trp 636 and Tyr 647/Thr 648 within the GluN1 TM3 and Trp 635 and Ser 645/Tyr 646/Thr 647 within GluN2B TM3 have been shown to regulate their surface delivery. These residues ensure subunits are retained in the ER until correct conformation of the TM3 domains is achieved to continue the forward trafficking (Horak et al, 2008a;Kaniakova et al, 2012).…”
Section: Cellular Events Involved In the Forward Trafficking And Memb...mentioning
confidence: 99%